Formation of Special Education Leadership Study Questionnaire Set That Influences The Task Load And Job Satisfaction Of Special Education Teachers In Malaysia - et. al., Nor Diana Mohd Idris, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Questionnaires are the most important instrument in research that uses a quantitative approach. Questionnaires were constructed to obtain empirical and rigid data related to a variable studied. Usually the questionnaire will use a certain scale in measuring the views of the respondents. The use of a set of questionnaires can facilitate researchers in collecting data collectively and can involve many respondents. The use of questionnaires also does not require specific time such as interview sessions or observations in a qualitative approach. Questionnaires can be constructed in two ways namely, adapting relevant previous questionnaires or constructing new items for the required questionnaires. This article review details the construction of a specific set of questionnaires for a study on the influence of school leadership on the workload and job satisfaction of teachers of special education integration program (PPKI) in the state of Johor, Malaysia. It is hoped that this survey can help future researchers in preparing the best set of questionnaires.